Differential kinetics of circulating angiotensin IV and II after treatment with angiotensin II type 1 receptor antagonist and their plasma levels in patients with chronic renal failure - Shibasaki, Y; Mori, Y; Tsutumi, Y; Masaki, H; Sakamoto, K; Murasawa, S; Maruyama, K; Moriguchi, Y; Tanaka, Y; Iwasaka, T; Inada, M; Matsubara, H (Clinical nephrology, 1999)
Angiotensin II (Ang II) C-terminal hexapeptide (referred to as Ang IV) possesses the characteristics of a real hormone with specific receptors and biological effects. Clinical application of Ang II type 1 receptor (AT1-R) antagonists cause an increase in plasma Ang II level, which may result in enhanced production of Ang IV. In this study, we measured plasma Ang IV and Ang II levels in patients with chronic renal failure (CRF), and also examined the changes in Ang IV and Ang II levels after administration of an ATI-R antagonist. Ang II and Ang IV levels in CRF patients untreated with hemodialysis (n = 16) were 15.8+/-3.6 and 6.0+/-1.1 pg/ml, respectively, which did not differ significantly from Ang II (20.6+/-2.4) and Ang IV levels (8.6+/-1.1) in normal controls (n = 23). The ratio of Ang IV to Ang II was 38%, similar to that in the controls (41%). Ang II or Ang IV levels in CRF patients treated with hemodialysis (n = 12) were also similar to the control values. Ang IV levels had a significant correlation with Ang II levels (r = 0.59). When hypertensive patients were treated with an AT1-R antagonist candesartan for 7 days, Ang II and Ang IV levels were increased 5.5- and 4.1-fold relative to the control levels, respectively. Ang II levels 28 and 56 days after treatment were significantly lower than those 7 days after treatment, whereas Ang IV levels did not differ significantly from those 7 days after treatment. Similar differential kinetics in Ang II and Ang IV levels after long-term (90 days) treatment with an AT1-R antagonist was also confirmed in experiments using rats. Significant decrease in blood pressure continued during long-term treatment with an AT1-R antagonist. These findings demonstrated that plasma Ang IV levels in patients with CRF did not differ significantly from those in normal subjects, and that treatment with an AT1-R antagonist caused marked increases in both Ang II and Ang IV levels. In contrast, during long-term treatment plasma Ang II levels were more rapidly decreased than Ang IV levels, suggesting longer-lasting enhancement of the action of Ang IV rather than that of Ang II after treatment with an AT1-R antagonist.